Sweetpotato support platforms to build a community of practice - International Potato Center (2011)
Three Sweetpotato Support Platforms (SSPs), located in Uganda, Mozambique, and Ghana are developing tools and strategies for sharing information and efficiencies to create a dynamic and cost-effective community of practice among researchers and development agents across multiple disciplines and countries. Through the Reaching Agents of Change project, launched in June 2011, they also aim to raise the profile of vitamin A-rich sweetpotato through advocacy and integrate “everything you ever wanted to know about sweetpotato” training efforts into the platform agenda.